Peningkatan Kemampuan Mengatasi Masalah Stunting dan Kesehatan melalui Pemberdayaan Masyarakat Desa Sukogidri, Jember - Erma Sulistyaningsih; Parawita Dewanti; Pulong Wijang Pralampita; Wiji Utami (Jurnal Pengabdian Pada Masyarakat, 2020)
INCREASING THE ABILITY IN OVERCOMING STUNTING AND HEALTH PROBLEM BY COMMUNITY EMPOWERMENT IN SUKOGIDRI VILLAGE, JEMBER. Indonesia has a high prevalence of stunting, and Jember is one of the six districts in East Java province that contribute to stunting prevalence. To overcome the stunting problem, it needs a holistic strategy including health, education and economic aspects, therefore the community empowerment is an important approach. The purpose of this public service program was to increase the awareness and capability of the community to overcome stunting and health problem by community empowerment. Several activities were conducted in this community service program, i.e. by examining the health status of the children, pregnant woman, and high risk people, counseling and education about stunting and the effect on health status and also the effect for the next generation, education about the efforts to prevent stunting, provide training to prepare a healthy food and specific training for the cadres who responsible for the stunting-alleviation program. The impact of the activity was an increase the knowledge and awareness of the community about stunting. And there were several trained-cadres about stunting and its prevention.